2012
DOI: 10.1177/0950017011432917
|View full text |Cite
|
Sign up to set email alerts
|

The open-plan academy: space, control and the undermining of professional identity

Abstract: The introduction of open-plan (OP) academic offices is critically examined through interviews undertaken in Scotland and Australia. The development is discussed in the context of the increased managerialism in higher education. The conclusion is that, despite a rhetoric of synergy, the dominant rationale for OP is one of cost reduction and that the experience for many academics is proving detrimental to both scholarship and professional identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 19 publications
2
101
0
11
Order By: Relevance
“…During this phase, the openplan office mirrored a factory, and desks were lined up in rows that all faced in the same direction (Savil, 2010). The typical office worker was imagined to be a clerical worker who produced standardised output and could be easily substituted (Baldry & Barnes, 2012). Early open-plan offices typically lacked barriers and were environments where employees could be 1 Taylorism (also known as Scientific Management) was an approach to management advocated by Frederick Taylor that involved analysing workflow and the movements of employees (Statt, 2004).…”
Section: A Short History Of Research On Physical Work Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…During this phase, the openplan office mirrored a factory, and desks were lined up in rows that all faced in the same direction (Savil, 2010). The typical office worker was imagined to be a clerical worker who produced standardised output and could be easily substituted (Baldry & Barnes, 2012). Early open-plan offices typically lacked barriers and were environments where employees could be 1 Taylorism (also known as Scientific Management) was an approach to management advocated by Frederick Taylor that involved analysing workflow and the movements of employees (Statt, 2004).…”
Section: A Short History Of Research On Physical Work Environmentmentioning
confidence: 99%
“…As a reaction against the alienation of bull-pen open-plan offices, the Bürolandschaft (or landscape office) was invented in Germany in the 1950s (Baldry & Barnes, 2012). In this phase of office design, plants and natural elements were brought into the office to demark groups of workers and provide some privacy (Baldry, 1997).…”
Section: A Short History Of Research On Physical Work Environmentmentioning
confidence: 99%
“…Compared to private offices, the amount of environmental distraction in open-plan offices are higher and more such as excessively noise, lack of privacy, presence of others, increased workloads, social setting problems and ambient conditions (Baldry and Barnes, 2012;Duval et al, 2002;Jahncke et al, 2011;Rashid et al, 2009;Banbury and Berry, 2005;Roelofsen, 2008). These problems and distractions are often suggested to reduce the end-users' satisfaction (both environmental and job satisfaction) (O'Neill, 2008;Lee and Brand, 2005), enhance physiological stress (Rasila and Rothe, 2012;Lee and Brand, 2010), reduce outcome including productivity and creativity (Davis et al, 2011;Elsbach and Pratt, 2007;Hua, 2007;Sundstrom et al, 1982;Davis, 1984;Carnevale, 1992;Baldry and Barnes, 2012;Lee and Brand, 2010;Miller, 2005) and increasing desire to work in private rooms (Lee and Brand, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In saving space, they decrease maintenance costs and make it possible for greater numbers of people to work together. Open-space designers also maintain that these work environments facilitate individual interaction and enhance collaboration (Baldry & Barnes, 2012;Brennan et al, 2002;Hua, 2007;Navai & Veitch, 2003;Samani, et al, 2017a). On the downside, open-plan offices have been shown to lead to interruptions, more stress, and lower levels of concentration (Brand, 2009;Samani et al, 2017b), which are all disadvantageous to individual and overall organizational outcome.…”
mentioning
confidence: 99%
“…Working in appropriate working conditions can enhance and improve employees' environmental satisfaction, well-being, and overall performance and organizational outcomes. In terms of office design, open-plan workspaces offer a low level of personal control and privacy and increased density, which could lead to distraction and adversely affect individual satisfaction with the work environment and even organizational outcomes (Baldry & Barnes, 2012;Hwang & Kim, 2013;Marquardt, Veitch, & Charles, 2002;Samani, Rasid, & Sofian, 2017a, 2017b.The results of the study conducted at PNPI Group's remodeled offices show that most of the respondents (61.6%) indicated that the change in design gave them more control over their workspace and that their satisfaction increased as a result of being able to personalize their own workstations and control the level of lighting. …”
mentioning
confidence: 99%